2019
DOI: 10.1038/s41576-019-0159-6
|View full text |Cite
|
Sign up to set email alerts
|

Nascent RNA analyses: tracking transcription and its regulation

Abstract: The genome encodes information to program an organism's development and maintenance, and its decoding begins with regulated transcription of genomic DNA into RNA. Transcription and its control can be tracked indirectly by measuring stable RNAs, or directly by measuring nascent RNAs. The latter reveals the immediate regulatory changes in response to developmental, environmental, disease, and metabolic signals. Multiple complementary methods have been developed to quantitatively track nascent transcription genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
180
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(184 citation statements)
references
References 222 publications
(228 reference statements)
4
180
0
Order By: Relevance
“…NET-seq captures nascent RNAs bound to transcriptionally engaged RNAPII and sequences the 3'-end of the purified RNAs, thus providing a detailed map of elongating RNAPII across the genome at nucleotide resolution . Although the term "nascent RNAs", has been frequently used in the literature to describe newly synthesized RNAs that are not necessarily associated with RNAPII (Wissink et al, 2019), it is supposed to refer to the RNA associated with the polymerase active centre. We will therefore refer to the transcripts captured by NET-seq as "nascent RNAs".…”
Section: Sensitivity To Transcription Elongation Stress and Accumulatmentioning
confidence: 99%
“…NET-seq captures nascent RNAs bound to transcriptionally engaged RNAPII and sequences the 3'-end of the purified RNAs, thus providing a detailed map of elongating RNAPII across the genome at nucleotide resolution . Although the term "nascent RNAs", has been frequently used in the literature to describe newly synthesized RNAs that are not necessarily associated with RNAPII (Wissink et al, 2019), it is supposed to refer to the RNA associated with the polymerase active centre. We will therefore refer to the transcripts captured by NET-seq as "nascent RNAs".…”
Section: Sensitivity To Transcription Elongation Stress and Accumulatmentioning
confidence: 99%
“…Regulation of the transcription cycle has been a topic of intense research and has been characterized in detail (Chen, Smith, and Shilatifard 2018;Jonkers and Lis 2015;Shandilya and Roberts 2012;Wissink et al 2019). General transcription factors bind to a nucleosome-free promoter causing conformational changes in the DNA helix that allow the binding of Pol II and concomitant synthesis of nascent RNA from the TSS.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide ChIP-seq analysis has shown that Pol II accumulates across the promoter proximal region (~-100-+300) including the TSSs and TPSs of most protein coding genes (Chen, Smith, and Shilatifard 2018;L. Core and Adelman 2019;Fraser, Sehgal, and Darnell 1978;Gariglio, Bellard, and Chambon 1981;Jonkers and Lis 2015;Kim et al 2005;Muse et al 2007;Wissink et al 2019;Zeitlinger et al 2007). It has been proposed that the density of Pol II found at the promoter proximal region represents paused Pol II and the ratio of this to the density of Pol II throughout the remainder of the body of the gene (the pausing index) has been used as a measure of transcriptional pausing (Muse et al 2007;Rahl et al 2010;Zeitlinger et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach was included 23 in the INSPEcT Bioconductor package, which can now unveil RNA dynamics from steady state or 24 time course data, with or without the profiling of nascent RNA. 25 Main 26 Since the development of microarrays first, and high-throughput sequencing later on, the 27 investigation of the transcriptional activity of genes has been mostly based on the quantification of 28 total RNA (Mortazavi et al, 2008). While bringing about a revolution in the field of transcriptional 29 regulation, the quantification of absolute and differential expression provides only a glimpse of the 30 complexity of cellular gene expression programs.…”
mentioning
confidence: 99%